The Immunodominant T-Cell Epitopes of the Mycolyl-Transferases of the Antigen 85 Complex of M. tuberculosis - Huygen, Kris (Frontiers in Immunology, 2014)
The Ag85 complex is a 30-32 kD family of three proteins (Ag85A, Ag85B and Ag85C), which all three possess enzymatic mycolyl-transferase activity involved in the coupling of mycolic acids to the arabinogalactan of the cell wall and in the biogenesis of cord factor. By virtue of their strong potential to induce Th1 type immune responses, important for the control of intracellular infections, members of the Ag85 family rank among the most promising TB vaccine candidate antigens. Ag85A and Ag85B, initially purified from M. bovis BCG/ M. tuberculosis culture filtrate respectively, induce strong T cell proliferation and IFN-g production in most healthy individuals latently infected with M. tuberculosis and in BCG vaccinated mice and humans but not in tuberculosis patients. Members of the Ag85 complex are highly conserved in other mycobacterial species. Mice and humans infected with M. ulcerans or cattle infected with M. bovis or M. avium subsp. paratuberculosis also show strong T cell responses to this protein family. Using synthetic overlapping peptides, bio-informatic prediction programs and tetramer-binding studies, a number of immunodominant CD4+ and CD8+ T cell epitopes have been identified in experimental animal models as well as in humans, using proliferation and Th1 cytokine secretion as main read-outs. The results from these studies are summarized in this review.